A Novel Approach for Efficient Web Data Collection - Edyta FRĄSZCZAK (Communications of International Proceedings, 2024)
Websites are becoming increasingly popular and contain a vast amount of unstructured data. This data is often collected and transformed into vector representations, which can be utilized in various domains such as marketing, SEO, and cybersecurity. This article introduces a new solution called Web2Vec (Website To Vector), designed to extract features from websites and convert them into vector formats. These vectorized representations can be applied across different applications, improving analysis and decision-making processes in multiple fields.
Keywords: Website data collection; structuring unstructured website data; website data vectorization; data mining.